PENGELOLAAN SAMPAH DI KOTA SEMARANG UNTUK MENUJU KOTA BERSIH - Hariyanto, -; Ariyani, - (Faculty of Social Science, Universitas Negeri Semarang, 2011)
Waste is derived from human activites. The amount or volume of waste is equivalent with level of material consumption used everday. The growth of population and socety economic growth will increase waste production. Population growth of Semarang City in 2003-2008 is 1,48% with the amount of populatioan is 1,48 millionÃ‚Â (2008). The certainly will create big amount of waste. The aim of this research is 1) to know how big is the amount of waste volume produced dy Semarang citizen, 2) to know how is the waste management in Semarang City to achieve Ã¢â‚¬Å“Adipura CityÃ¢â‚¬Â. Research methodology which is used is quantitative descriptive. Research population is the citizen of Semarang City, the sample is 70 family head taken using purposive random sampling. The result of the research shows that the volume waste produced is 1.000-1.500 ton per day, with waste development 8-12% per year. Waste volume is infuenced by the number of person in each family, economic level and kind of activities. From that volume, 61,2% is industri waste and in the rest is non-industri. In the case of waste management, only 31% of waste is taken to fnal disposal, 53% of waste is burnt or burried, 15% is thrown to river/ditch, and 1,5% of waste is made compost. The society regards maste problem as government bussines, not personal individual bussines. Waste management approach emphasizes more on post-production waste management, instead of directing to the effort to decrease waste volume before production. Keywords: Waste, waste management